Parosteal Lipoma of the Humerus: A Case Report - Das, Deependra; Jinbai, Huang (Janaki Medical College Journal of Medical Science, 2017)
Background and Objectives: To study the imaging and histopathological characteristic of a tumorous mass and to differentiate parosteal lipoma from similar looking osteochondroma or myositis ossificans. Presentation of case: A 54-year old female presented with more than 5-years history of a large swelling in the anterolateral aspect of upper arm. The case study was carried out at the First Hospital of Yangtze University situated in Jingzhou city of Hubei province, PRC in 2015 September. Discussion: Radiological Imaging and Pathological examination confirmed the diagnosis of parosteal lipoma. Computed tomography (CT) and Magnetic Resonance Imaging (MRI) showed the mass to be fatty in nature with characteristic pedunculated exostosis abutting the periosteum. Histopathological sections showed the mass to be composed of mature adipose tissue without atypia or lipoblast. Conclusion: Parosteal lipomas are rare neoplasias with no proven malignant potential and requires high index of suspicion for proper diagnosis and effective management. Janaki Medical College Journal of Medical Sciences (2016) Vol. 4 (2): 41-45